Cyprus Sausages' Bacterial Community Identification Through Metataxonomic Sequencing: Evaluation of the Impact of Different DNA Extraction Protocols on the Sausages' Microbial Diversity Representation - Kamilari, Eleni; Efthymiou, Marina; Anagnostopoulos, Dimitrios A.; Tsaltas, Dimitrios (My University, 2021)
Cyprus traditional sausages from the Troodos mountainous region of Pitsilia gained the protected geographical indication (PGI) designation from the European Committee (EU 2020/C 203/06). Still, we lack authentication protocols for the distinction of "Pitsilia" from industrially produced Cyprus sausages. Microbial activity is an essential contributor to traditional sausages' sensorial characteristics, but whether the microbial patterns might be associated with the area of production is unclear. In the present research, we applied high-throughput sequencing (HTS) to provide a linkage between the area of production and Cyprus sausages' bacterial diversity. To strengthen our findings, we used three different DNA extraction commercial kits: (i) the DNeasy PowerFood Microbial Kit (QIAGEN); (ii) the NucleoSpin Food Kit (MACHEREY-NAGEL); and (iii) the blackPREP Food DNA I Kit (Analytik Jena), in which we applied three different microbial cell wall lysis modifications. The modifications included heat treatment, bead beating, and enzymatic treatment. Results regarding metagenomic sequencing were evaluated in terms of number of reads, alpha diversity indexes, and taxonomic composition. The efficacy of each method of DNA isolation was assessed quantitatively based on the extracted DNA yield and the obtained copy number of (a) the 16S rRNA gene, (b) the internal transcribed spacer (ITS) region, and (c) three Gram-positive bacteria that belong to the genera Latilactobacillus (formerly Lactobacillus), Bacillus, and Enterococcus via absolute quantification using qPCR. Compared with some examined industrial sausages, Pitsilia sausages had significantly higher bacterial alpha diversity (Shannon and Simpson indexes). Principal coordinates analysis separated the total bacterial community composition (beta diversity) of the three Pitsilia sausages from the industrial sausages, with the exception of one industrial sausage produced in Pitsilia, according to the manufacturer. Although the eight sausages shared the abundant bacterial taxa based on 16S rDNA HTS, we observed differences associated with bacterial diversity representation and specific genera. The findings indicate that the microbial communities may be used as an additional tool for identifying of the authenticity of Cypriot sausages.
Keywords: 16S rDNA sequencing; DNA extraction protocols; Bacterial diversity; Metagenomics; Metataxonomic; Sausages